2014
DOI: 10.3174/ajnr.a4038
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium Enhancement of Atherosclerotic Plaque in the Middle Cerebral Artery: Relation to Symptoms and Degree of Stenosis

Abstract: BACKGROUND AND PURPOSE: High-resolution MR imaging can depict intracranial arterial atherosclerotic plaques. Our aim was to evaluate the relationship between the degree of enhancement of MCA plaques on contrast-enhanced high-resolution MR imaging and ischemic stroke and stenosis severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…Contrast‐enhanced VWI sequences might be useful for the depiction of VWLs of the distal MCA beyond the M3 segment, according to a review of the literature in CNS vasculitis that showed arterial wall enhancement due to increased permeability of the endothelium with contrast leakage from the lumen into the arterial wall . Furthermore, a previous study identified a significant association between plaque enhancement on intracranial arteries and ischemic events . Therefore, further studies with contrast‐enhanced materials will be needed to assess small arteries, such as the M3 branches and distal arteries.…”
Section: Discussionsupporting
confidence: 60%
“…Contrast‐enhanced VWI sequences might be useful for the depiction of VWLs of the distal MCA beyond the M3 segment, according to a review of the literature in CNS vasculitis that showed arterial wall enhancement due to increased permeability of the endothelium with contrast leakage from the lumen into the arterial wall . Furthermore, a previous study identified a significant association between plaque enhancement on intracranial arteries and ischemic events . Therefore, further studies with contrast‐enhanced materials will be needed to assess small arteries, such as the M3 branches and distal arteries.…”
Section: Discussionsupporting
confidence: 60%
“…There are increasing evidence of the presence of plaque and pattern of enhancing plaque in patients with ICAS. 16,17 Results of others and our studies showed that plaques tend to locate opposite to the orifices of perforating arteries. 18 However, few studies have reported about the remodeling pattern in patients with ICAS.…”
Section: Ryoo Et Al Differential Vascular Pathophysiologies Of Icas 2819mentioning
confidence: 96%
“…Although the specific time when reperfusion occurred cannot be determined for the tPA-alone group, faster time from symptom onset to reperfusion (modified thrombolysis in cerebral infarction score of 2b or 3) was significantly associated with functional independence in the intervention group (P<0.01). 17 Both the intervention group and the control patients who did not reperfuse had poor clinical outcomes (≈80% were disabled at 90 days). Infarct growth and 27-hour infarct volume were substantially larger in nonreperfusers in both treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…These papers have described that intracranial plaque enhancement on MRI can help identify lesions responsible for an ischemic event and can potentially serve as a marker of intracranial plaque instability and stroke risk 4 . It has also been described that plaque enhancement was significantly higher in patients with symptomatic plaques in accordance with the degree of stenosis 6 . Recently, three-dimensional contrast-enhanced, high-resolution, black-blood MRI has been applied to investigate atherosclerotic lesions, which not only accurately detects atheroma burden, but also gives information regarding atheroma composition such as necrotic core, intraplaque hemorrhage, inflammation, and neovascularization 7 .…”
Section: Introductionmentioning
confidence: 90%
“…Skarpathiotakis et al 3 , Qiao et al 4 , Natori et al 5 , and Ryu et al 6 . These papers have described that intracranial plaque enhancement on MRI can help identify lesions responsible for an ischemic event and can potentially serve as a marker of intracranial plaque instability and stroke risk 4 .…”
Section: Introductionmentioning
confidence: 99%